Current Prospects of Rome Criteria for the Diagnosis of Irritable Bowel Syndrome - Shammout, Rasha Zaid; Ahmad, Mousa Numan (Jordan Journal of Agricultural Sciences, 2022)
Irritable bowel syndrome (IBS) is a worldwide health problem. It is often diagnosed by periodically- updated Rome symptom-based criteria, but the effects of recent updates on IBS diagnosis are not well clarified. This article overviews Rome III and IV IBS criteria, highlighting changes and updates that may impact IBS diagnosis. PubMed, Medline, Science Direct, Clinical trials.gov, and WHO databases were searched through to July 2021. Rome IV criteria are more restrictive, specific, and precise in patients′ diagnosis, selection, prognosis, and follow-up than Rome III criteria, in turn, IBS prevalence and number of patients with IBS-unspecified and IBS-mixed subtypes decrease, but overall symptom severity and patients′ homogeneity increase. In essence, the slight difference between Rome III and IV criteria reflects a considerable influence on IBS diagnosis, subtyping, and prevalence. Rome IV IBS patients form a homogeneous subset of Rome III IBS patients with more severe symptoms. Thus, in-depth research is warranted.